Telehealth and telemedicine projections in the post-covid-19 era. A scoping review - Hechenleitner-Carvallo, Marcela; Ibarra-Peso, Jacqueline (Data and Metadata, 2025)
Introduction: Before the COVID-19 pandemic, telemedicine and telehealth faced legal, technological, and cultural regulatory limitations. The health crisis boosted its massive adoption, enhancing its continuity over time. The objective of this review is to determine the projections of telehealth and telemedicine in the post-COVID-19 era and the factors that condition its growth.Methods: A systematic review was carried out following the PRISMA-ScR guidelines. The databases consulted were PubMed, Web of Science, and Scopus. 19 relevant studies were selected from an initial total of 96.Results: The pandemic accelerated the adoption of telemedicine, maintaining its use in areas such as mental health and chronic diseases. Factors associated with the use and development of technologies, added to cultural and economic aspects, have hindered its growth.Conclusions: Telehealth and telemedicine have improved access to health, but their sustainability requires resolving technological inequalities, in addition to guaranteeing privacy and security standards.